Lanthanide‐Based Functional Misfit‐Layered Nanotubes1. (4th June 2014) - Panchakarla, Leela S.; Popovitz‐Biro, Ronit; Houben, Lothar; Dunin‐Borkowski, Rafal E.; Tenne, Reshef
Abstract The synthesis of nanotubes from layered compounds has generated substantial scientific interest. "Misfit" layered compounds (MLCs) of the general formula [(MX)1+x]m[TX2]n, where M can include Pb, Sb, rare earths; T=Cr, Nb, and X=S, Se can form layered structures, even though each sub‐system alone is not necessarily a layered or a stable compound. A simple chemical method is used to synthesize these complex nanotubes from lanthanide‐based misfit compounds. Quaternary nanotubular structures formed by partial substitution of the lanthanide atom in nanotubes by other elements are also confirmed. The driving force and mechanism of formation of these nanotubes is investigated by systematic temperature and time‐dependent studies. A stress‐inducement mechanism is proposed to explain the formation of the nanotubes. The resulting materials may find applications in fields that include thermoelectrics, light emitters, and catalysis and address fundamental physical issues in low dimensions.